Building Career Development Skills for Researchers: A Qualitative Study Across Four African Countries - Halima Okewole; Christopher Merritt; Walter Mangezi; Victoria Mutiso; Helen E. Jack; Thalia C. Eley; Melanie Abas (Ubiquity Press, 2020)
Background: Career development skills are widely advocated as part of research capacity building and strengthening efforts. However, there is a gap in knowledge on their acceptability in low- and middle-income countries. Objective: This study aimed to examine how a group of 16 early-career researchers in sub-Saharan Africa experienced a career development skills course and how they perceived the utility of the course. Methods: Sixteen early-career researchers registered at universities in Ethiopia, Zimbabwe, Malawi, and South Africa took part in the year-long Academic Competencies Series (ACES) course. ACES comprised ten modules covering mentoring skills, work-life balance, career strategy, teamwork, presentation skills, teaching, academic writing, engaging policy makers, grant-writing, and digital media. ACES was delivered through face-to-face workshops and via webinar as part of a broader mental health research capacity-building programme. In-depth interviews following a topic guide were conducted with participants. Interviews were recorded and transcribed verbatim. Data were analysed using Thematic Analysis. Findings: All ACES participants were interviewed (9 male, 7 female). Participants were PhD students (14) and post-docs (2). The main themes identified throughout the course were 1) Growth, in both personal and professional life; 2) Application of training, often in innovative ways but with notable constraints and obstacles; and 3) Connection with colleagues, where researchers learnt from each other and from experts, building confidence in their new skills. Participants described how face-to-face contact enhanced the perceived quality of their learning experience. Barriers included logistical obstacles to applying training, such as limited resources and being at an early career stage. Conclusions: We found that research career development skills training was highly acceptable for early-career researchers in four African countries, and was perceived as having facilitated their personal and professional growth. Our findings suggest that courses like ACES can be applied successfully and innovatively in low-income settings.